An investigation of the compatibility of nickel-based single crystal superalloys with thermal barrier coating systems - Wu, RT; Kawagishi, K; Harada, H; Reed, R (2008)
The compatibility of a number of nickel-based single crystal superalloys with a thermal barrier coating (TBC) system is examined. An industry-standard yttria-stabilised zirconia (YSZ)-type ceramic was used throughout this work, deposited using electron beam physical vapour deposition at a commercial facility. It is demonstrated that the resistance to spallation during thermal cycling is dependent upon the composition of the superalloy substrate upon which the TBC system is placed - the number of cycles to failure is found to vary by up to a factor of three when identical TBC systems (bond coat, ceramic layer) are employed. Of the three different bond coat systems considered, a platinum-diffused (so-called low-cost bond coat) was found to be consistently better than both low-activity or high-activity platinum aluminide bond coats, but only marginally. The composition of the superalloy substrate is thus shown to be the primary factor in determining TBC life.